Pengenalan dan Pelatihan Pembuatan Minuman Herbal Eliksir Telang Rempah Sembilan kepada Ibu-Ibu Senam - Sardi Pranata; Ivana Anelia Samosir; Nur Rahma Pitriani; Fani Viona Siallagan; Esra Siagian; Santi Antasia Rumahorbo; Pritti Sinta Sihite; Sanni Sirait; Pilda Wardani (Jurnal Kemitraan Masyarakat, 2025)
This study aims to describe the implementation and outcomes of training on making herbal elixir beverages from nine spice butterfly pea ingredients for exercise mothers as an effort to improve knowledge and skills in processing healthy drinks. The activity was motivated by the limited use of herbal beverages after exercise and the low level of public understanding regarding the benefits of butterfly pea flowers and traditional spices as natural stamina enhancers. The study applied a descriptive qualitative approach through observation and documentation conducted from November 22 to December 5, 2025. A total of 25 exercise mothers participated in the training, which consisted of demonstrations and direct practice in preparing elixirs using dried butterfly pea flowers combined with ginger, turmeric, galangal, lemongrass, cinnamon, cloves, betel leaves, and brown sugar. The results show that participants were able to follow all training stages properly and demonstrated increased understanding of herbal benefits, ingredient functions, dosage accuracy, and processing procedures. Achievement indicators reveal that 92 percent of participants were able to independently prepare the elixir according to the demonstrated steps, 84 percent were able to explain the function of each ingredient correctly, and all groups successfully produced elixir products with color, aroma, and taste that met the expected standards. Participants also responded positively and expressed interest in reapplying the recipes at home and developing flavor variations for personal consumption or small scale business opportunities effectively.